1999
DOI: 10.1007/s005850050856
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the first Schumann resonance frequency during relativistic solar proton precipitation in the 6 November 1997 event

Abstract: Abstract. The variations of the ®rst mode of Schumann resonance are analyzed using data from Kola peninsula stations during the solar proton event of 6 November 1997. On this day the intensive¯ux of energetic protons on GOES-8 and the 10% increase of the count rate of the neutron monitor in Apatity between 1220 and 2000 UT were preceded by a solar X-ray burst at 1155 UT. This burst was accompanied by a simultaneous increase of the Schumann frequency by 3.5%, and the relativistic proton¯ux increase was accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…During solar activity there may be two kinds of changes: (1) increase in ionization level at the normal D-region reflection heights, and (2) the variation of D-region's lower edge (Roldugin et al 1999). According to this model the variation in the first SR frequency is given by (Roldugin et al 1999) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During solar activity there may be two kinds of changes: (1) increase in ionization level at the normal D-region reflection heights, and (2) the variation of D-region's lower edge (Roldugin et al 1999). According to this model the variation in the first SR frequency is given by (Roldugin et al 1999) .…”
Section: Resultsmentioning
confidence: 99%
“…This fact contributes additionally to the increase in the first SR frequency. During a SPE energetic protons can penetrate deeply into the ionosphere up to 50 km and can ionize regions lower than the normal D-region (Roldugin et al 1999;Clilverd et al 2006). In this case h 1 changes by the value 1 d .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Any change in the electrons density in lower ionosphere modifies its dielectric permeability, which plays an important role in modifying the SR frequency. Roldugin et al (1999) showed that the SR frequency depends both on the electron density in the ionospheric Dregion and on the base height of this region. For the interpretation of our data, we now consider, in some detail, the simple model of Roldugin et al (2003), for which the authors establish a quantitative relation between SR frequencies and the ionospheric parameters.…”
Section: Estimation Of Electron Density In Lower Ionospherementioning
confidence: 99%